2023
DOI: 10.1021/acs.est.2c03596
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Total Organic Halogen Formed during Chlorination: The Iceberg of Halogenated Disinfection Byproducts Was Previously Underestimated

Abstract: Total organic halogen (TOX) is widely used as a surrogate bulk parameter to measure the overall exposure of halogenated disinfection byproducts (DBPs) in drinking water. In this study, we surprisingly found that the level of TOX in chlorinated waters had been significantly underestimated under common analytical conditions. After the addition of quenching agent sodium thiosulfate, total organic chlorine and total organic bromine exhibited a two-phase decomposition pattern with increasing contact time, and a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…FT-ICR MS has emerged as a reliable analytic tool for the nontargeted screening of unknown halogenated DBPs. , To identify the N-DBP formation in the pipes, negative-ion ESI-FT-ICR mass spectra are shown in Figure S3, and the distribution and the number of N-DBPs in the samples corresponding to different scenarios are shown in Figures and S4. For all three pipes, the relative intensities of N-DBPs were all stronger under “NO 3 – -Rich” conditions than in the “Blank”.…”
Section: Resultsmentioning
confidence: 99%
“…FT-ICR MS has emerged as a reliable analytic tool for the nontargeted screening of unknown halogenated DBPs. , To identify the N-DBP formation in the pipes, negative-ion ESI-FT-ICR mass spectra are shown in Figure S3, and the distribution and the number of N-DBPs in the samples corresponding to different scenarios are shown in Figures and S4. For all three pipes, the relative intensities of N-DBPs were all stronger under “NO 3 – -Rich” conditions than in the “Blank”.…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial to determine adequate quenching agent and dose to achieve simultaneous disinfection termination and DBP preservation. Commonly used quenching agents (i.e., ascorbic acid, sodium thiosulfate, and sodium sulfite) might degrade the DBPs in the range of 18–100%. However, it was found that ammonium chloride, as the quenching reagent, could achieve a minor or no degradation of target DBPs within 48 h . Therefore, samples were quenched with ammonium chloride at a molar ratio of 1:1.3 free chlorine to quenching agent and then acidified to pH 3.0–5.0 using sulfuric acid.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the complexity of DBPs and the fact that numerous DBPs are still unknown, total organic halogen (TOX) has been used as a surrogate indicator to represent all halogenated organic DBPs in chlorinated drinking water. 31,66,67,69,70 In addition, studies have reported that for the same source water, the TOX concentration generally correlates positively with the toxicity of a chlorinated drinking water sample, 4,65,66,71,72 indicating that TOX may be a suitable indicator to represent or predict the toxicity of DBP mixtures in a water sample.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This study was therefore designed to (1) quantify the contributions of NOM and pharmaceuticals to the overall formation of halogenated DBPs; (2) establish a kinetic model for predicting the halogenated DBP formation and the relative contributions in chlorination of source waters containing both NOM and pharmaceuticals; and (3) evaluate the developmental toxicity of NOM- and pharmaceutical-derived DBPs and their combined effects on the overall developmental toxicity of DBP mixtures. Because of the complexity of DBPs and the fact that numerous DBPs are still unknown, total organic halogen (TOX) has been used as a surrogate indicator to represent all halogenated organic DBPs in chlorinated drinking water. ,,,, In addition, studies have reported that for the same source water, the TOX concentration generally correlates positively with the toxicity of a chlorinated drinking water sample, ,,,, indicating that TOX may be a suitable indicator to represent or predict the toxicity of DBP mixtures in a water sample.…”
Section: Introductionmentioning
confidence: 99%